Vocês estão me ouvindo?: a escrita da violência do Estado - Carreiro, Lucia Filomena (2022)
The deaths of young people due to the State violence, most of them black and living in the periphery, causes deep psychosocial impacts on their mothers, family, friends, and territories. Theses impacts are restated through a policy of silencing driven by the State, thus reigning the dominant version of racialized criminalization of poverty. This work, carried out by the Movimento Mães em Luta da Zona Leste (SP), which involves mothers and family members who lost their children murdered by State agents, seeks to bring subsidies as to the ways of constitution of clinical-political devices of care for the suffering experienced by them. As a way of making society aware of State violence and producing memory, the participants of the Movement expressed the desire to write a book, built collectively through a Group Writing device. This was accomplished by six mothers and an aunt and took place on remote basis from September 2020 to February 2021. The record of verbal and pre-verbal material, read at each workshop meeting, was systematically made by the researcher. A field report was made, too. That material, built in the form of narratives, contains the field of methodological reflections and clinicalethical-political aspects of this research; these reflections are articulated with the discussions of institutional analysis, as well as the Améfrico Ladinos feminisms, the Reformation Psychiatry, and studies on state violence and racism. The narratives circumscribe three movements: “write and enunciate the sensible”, that takes place when the writing device is presented and the encounter between researcher-mothers happen; "you are listening to me?” that focuses on “listening” to the psychosocial impacts of state violence operated in mental health and care policy, based on the rhetoric of “listening to qualified”; and, finally, in the “vibrating memory” movement, we point to listening to the sensitive as an insurgent and non-passivating practice of welcoming the affections that ask for passage, contributing to the experience of a memory of the body as a mode of health production